HAZIRLIK SINIFI ÖĞRENCİLERİNİN BİLİŞÜSTÜ FARKINDALIKLARI, ÖZ - YETERLİK ALGILARI, YABANCI DİLE YÖNELİK KAYGILARI, TUTUMLARI VE AKADEMİK BAŞARILARININ İNCELENMESİ - DOĞAN, YUNUS (Fırat Üniveristesi, 2016)
Bu araştırmada 2013-2014 akademik yılında Fırat Üniversitesi'nin çeşitli mühendislik fakültesi bölümlerini kazanmış ancak zorunlu İngilizce hazırlık eğitimi alma gerekliliğince Yabancı Diller Yüksek Okulunda İngilizce hazırlık eğitimi almakta olan öğrencilerin genel bilişüstü farkındalıkları, akademik öz-yeterlik algıları, yabancı dil ders kaygıları, yabancı dile yönelik tutumları ve yabancı dilde akademik başarıları arasındaki ilişkiler incelenmiştir. Ayrıca öğrencilerin genel bilişüstü farkındalık, akademik öz-yeterlik algı, yabancı dil ders kaygısı, yabancı dile yönelik tutum ve yabancı dilde akademik başarı düzeyleri ve bunların cinsiyet, bölüm, mezun olunan Lise türü, Öğretim türü, yurt-dışı deneyimi, algılanan gelir düzeyi ve Türkçe ve İngilizce dışında bilinen başka bir dil değişkenleri açısından farklılaşıp farklılaşmadığı da araştırılmıştır. İlişkisel tarama modelinde yürütülen bu araştırmanın çalışma evreni 683 öğrenciden oluşmaktadır. Araştırma verileri, kişisel bilgi formu, Yabancı Dil Ders Kaygısı Ölçeği, İngilizce Dersine Yönelik Tutum Ölçeği, Bilişüstü Farkındalık Envanteri ve Akademik Öz-yeterlik Ölçeği ile elde edilmiştir. Ayrıca, F.Ü Y.D.Y.O'undan alınan öğrenci notlarına ilişkin veriler kullanılmıştır. Araştırma verileri, yüzde, frekans, ortalama, standart sapma, t-testi, ANOVA ve yapısal eşitlik model testi gibi istatistiksel yöntemlerle analiz edilmiştir. Araştırma sonucunda elde edilen bazı bulgular şunlardır: 1. Öğrencilerin akademik öz-yeterlik algısı ile yabancı dilde akademik başarıları arasında pozitif yönde anlamlı bir ilişki vardır. 2. Öğrencilerin yabancı dil ders kaygıları ile yabancı dilde akademik başarıları arasında negatif yönde anlamlı bir ilişki vardır. 3. Öğrencilerin akademik öz-yeterlik algıları ile yabancı dil ders kaygıları arasında negatif yönde anlamlı bir ilişki vardır. 4. Öğrencilerin yabancı dil ders kaygılarıyla yabancı dilde akademik başarıları arasında öz-yeterlik algısının aracılık etkisi bulunmaktadır. 5. Öğrencilerin genel bilişüstü farkındalıkları ile yabancı dilde akademik başarıları arasında anlamlı bir ilişki bulunmamaktadır. 6. Öğrencilerin bilişüstü farkındalığı ile öz-yeterlik algıları arasında pozitif yönde anlamlı bir ilişki bulunmaktadır. 7. Öğrencilerin bilişüstü farkındalıkları ve yabancı dilde akademik başarıları arasında öz-yeterlik algılarının aracı etkisi bulunmaktadır. 8. Öğrencilerin yabancı dile yönelik tutumları ve yabancı dilde akademik başarıları arasında öz yeterlik algılarının aracı etkisi bulunmaktadır. Araştırma sonucunda, yabancı dil ders kaygısının yabancı dilde akademik başarı önünde önemli bir engel olduğu tartışılmış, yabancı dil kaygısının aşılmasında ve öğrencilerin yabancı dil dersine yönelik pozitif tutum oluşturmalarının sağlanmasında öz-yeterlik algıları ve bilişüstü farkındalığın rolü vurgulanmıştır. Araştırmada, son olarak araştırmanın sonuçları bağlamında eğitim uygulayıcı ve araştırmacılarına önerilerde bulunulmuştur. Anahtar Kelimeler: Yabancı Dil Öğrenimi, Bireysel Farklar, Üstbilişsel Farkındalık, Öz-yeterlik, Yabancı Dil Kaygısı, Yabancı Dile Yönelik Tutum, Akademik Başarı

This dissertation aimed to examine the relations among the general metacognitive awareness levels, academic self-efficacy beliefs, foreign language classroom anxiety levels, foreign language attitudes and foreign language achievement of the Turkish students who, having been registered to study at various engineering departments of Fırat University, were receiving compulsory English preparatory education at the School of Foreign Languages during the academic year of 2013-2014. Moreover, the study also tried to investigate whether the students' general metacognitive awareness levels, academic self-efficacy beliefs, foreign language classroom anxiety levels, foreign language attitudes and foreign language achievement significantly differ in terms of their gender, department, the kind of high-school they already finished, the type of prep-class education they were receiving (daytime and evening education), their experience abroad, perceived level of income and any third language (other than Turkish and English) they knew. The population of this correlational survey study was consisted of 683 students. The data of the study were collected with a personal information sheet, the Foreign Language Classroom Anxiety Scale, the Attitudes towards English Scale, the Metacognitive Awareness Inventory, and the College Academic Self-Efficacy Scale. In addition, the data regarding the students' prep-class grades were taken from the School of Foreign Languages, Fırat University. In order to analyze the data of the study, such statistical techniques as percentage, frequency, mean, standard deviation, t-test, ANOVA and structural equation modelling were employed. Some of the findings of the study are as follow: 1. There is a statistically significant positive correlation between the students' academic self-efficacy beliefs and their foreign language achievement. 2. There is a statistically significant negative correlation between the students' foreign language classroom anxiety and their foreign language achievement. 3. There is a statistically significant negative correlation between the students' academic self-efficacy beliefs and their foreign language classroom anxiety. 4. The students' academic self-efficacy beliefs have a mediating effect on the relationship between their foreign language classroom anxiety and foreign language achievement. 5. There is no statistically significant correlation between the students' general metacognitive awareness and their foreign language achievement. 6. There is a statistically significant positive correlation between the students' metacognitive awareness and their academic self-efficacy beliefs. 7. The students' academic self-efficacy beliefs have a mediating effect on the relationship between their metacognitive awareness and foreign language achievement. 8. The students' academic self-efficacy beliefs have a mediating effect on the relationship between their attitudes toward English and foreign language achievement. As a conclusion, it was discussed in the study that foreign language classroom anxiety is a considerable hinderance in front of the achievement in foreign language learning, and the role of self-efficacy and metacognitive awareness were emphasized in order to combat against foreign language anxiety, and to enable learners to develop positive attitudes toward the foreign language classes. Lastly, the study was concluded with suggestions for future research and implications. Key Words: Foreign Language Learning, Individual Differences, Metacognitive Awareness, Self-efficacy, Foreign Language Anxiety, Foreign Language Attitudes, Academic Achievement
Examination of prep-class students' metacognitive awareness, self - efficacy beliefs, foreign language anxiety levels, foreign language attitudes and academic achievement in foreign language
Keywords: Eğitim ve Öğretim